2007
DOI: 10.1007/s10643-007-0179-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Role of Book Reading Practices in Indian Bilingual Children’s English Language and Literacy Development

Abstract: The goal of this study was to examine the role of Indian bilingual parentsÕ book reading practices on the development of the childrenÕs oral language, narrative and literacy skills in English, their second language. About 24 bilingual children from two preschools in Bangalore, India were tested in schools in English on receptive vocabulary, complex syntax, narrative expression, phonological awareness, and concepts about print. The findings suggest that exposure to book reading in English is associated with bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 10 publications
3
22
2
Order By: Relevance
“…All found relationships between parental literacy practices in their children’s L2 (as measured by either frequency of book reading or library usage) and children’s language outcomes in their second language (González & Uhing, 2008; Kalia, 2007; Patterson, 2002). However, the study by Farver, Xu, Eppe, and Lonigan (2006) found that the relationship between parental literacy activities and language outcomes was mediated by children’s interest in reading.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All found relationships between parental literacy practices in their children’s L2 (as measured by either frequency of book reading or library usage) and children’s language outcomes in their second language (González & Uhing, 2008; Kalia, 2007; Patterson, 2002). However, the study by Farver, Xu, Eppe, and Lonigan (2006) found that the relationship between parental literacy activities and language outcomes was mediated by children’s interest in reading.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Hammer, Miccio, and Wagstaff (2003) found no relationship between literacy events in the home and Spanish-English DLL children’s emergent literacy abilities in Head Start. However, studies by Kalia (2007) and Kalia and Reese (2009) identified a relationship between Indian parents’ book reading practices and teaching about print in English and children’s English literacy abilities. The difference between these findings may be accounted for by the parents’ educational status.…”
Section: Resultsmentioning
confidence: 99%
“…For each print-exposure study included, we then tried to find a match on four main characteristics: sample size, children's mean age, home language, and socioeconomic status. Except for one study with 24 English-speaking preschool children from India (Kalia, 2007), we were able to match each of the 15 studies with a comparable counterpart (see Appendix 2.1 and 2.2). This cross-validation approach gave us the unique opportunity to independently study differential effects of two measurement methods.…”
Section: Methods Search Strategy and Inclusion Criteriamentioning
confidence: 99%
“…These home experiences may make positive contributions to the overall growth of narrative abilities of bilingual children, as it is theorized that the ability to produce narratives develops as children engage in activities with their caregivers and are exposed to stories through books and literacy materials (Bruner, 1991;Curenton, 2010;Purcell-Gates, 1988). In order to investigate the impact of the home environment on narrative abilities, researchers have conceptualized the HLE as activities that expose children to stories, including shared book reading, maternal storytelling, children's participation in storytelling with their caregivers, and exposure to books in the home (Doiron & Shapiro, 1988;Kalia, 2007;Leseman, Scheele, Mayo, & Messer, 2007). The few studies that have focused on the HLE and its relationship to both concurrent and later narrative abilities have focused mainly on monolingual populations and are summarized below.…”
Section: Home Literacy Environmentmentioning
confidence: 99%
“…The aim of this study was to determine the relationship between the HLE and children's English microstructure and macrostructure development over 4 years, from 2 years of preschool through the end of first grade. It was hypothesized that the frequency of home literacy activities and the number of children's books in the home would contribute to the development of children's narrative abilities through the end of first grade (e.g., Doiron & Shapiro, 1988;Kalia, 2007;Leseman et al, 2007).…”
Section: Purpose Of the Studymentioning
confidence: 99%